Endothelin-1 increases expression and activity of arginase 2 via ETB receptors and is co-expressed with arginase 2 in human atherosclerotic plaques. (January 2020) - Rafnsson, Arnar; Matic, Ljubica Perisic; Lengquist, Mariette; Mahdi, Ali; Shemyakin, Alexey; Paulsson-Berne, Gabrielle; Hansson, Göran K.; Gabrielsen, Anders; Hedin, Ulf; Yang, Jiangning; Pernow, John
Abstract: Background and aims: Endothelin-1 (ET-1) and arginase are both suggested to be involved in the inflammatory processes and development of endothelial dysfunction in atherosclerosis. However, information regarding the roles of ET-1 and arginase, as well as the interactions between the two in human atherosclerosis, is scarce. We investigated the expression of ET-1 and its receptors, ETA and ETB, as well as arginase in human carotid atherosclerotic plaques and determined the functional interactions between ET-1 and arginase in endothelial cells and THP-1-derived macrophages. Methods: Carotid plaques and blood samples were retreived from patients undergoing surgery for symptomatic or asymptomatic carotid stenosis. Plaque gene and protein expression was determined and related to clinical characteristics. Functional interactions between ET-1 and arginase were investigated in endothelial cells and THP-1 cells. Results: Expression of ET-1 and ETB receptors was increased in plaques from patients with symptomatic carotid artery disease. ET-1 was co-localized with arginase 1 and arginase 2 in the necrotic core, together with macrophage markers CD163 and CD68. Arginase 2, ET-1 and ETB receptors were expressed in endothelial cells as well as in smooth muscle cells in the fibrous cap. ET-1 increased arginase 2 mRNA expression and arginase activity in endothelial cells and arginase activity in macrophages. Moreover, ET-1 stimulated formation of reactive oxygen species (ROS) in THP-1-derived macrophages via an arginase-dependent mechanism. Conclusions: This is the first study that demonstrates co-localization of ET-1 and arginase 2 in human atherosclerotic plaques. ET-1 stimulated arginase 2 expression and activity in endothelial cells, as well as arginase activity and ROS formation in macrophages via an arginase-dependent mechanism. These results indicate an important interaction between the ET pathway and arginase in human atherosclerotic plaques. Graphical abstract: Image 1 Highlights: ET-1 and its receptors ETA and ETB were highly expressed in endothelial cells, vascular smooth muscle cells and macrophages. ET-1 and arginase were localized in the necrotic core and closely associated. The expression of ET-1 and ETB receptors was increased in carotid plaques from symptomatic patients. ET-1 increased arginase expression and activity in endothelial cells and arginase activity in THP-1-derived macrophages. ET-1 stimulated reactive oxygen species formation in THP-1-derived macrophages via an arginase-dependent mechanism.